Persistence of health inequalities in childhood injury in the UK: a population-based cohort study of children under 5. - Elizabeth Orton; Denise Kendrick; Joe West; Laila J Tata (PLoS ONE, 2014)
Injury is a significant cause of childhood death and can result in substantial long-term disability. Injuries are more common in children from socio-economically deprived families, contributing to health inequalities between the most and least affluent. However, little is known about how the relationship between injuries and deprivation has changed over time in the UK.We conducted a cohort study of all children under 5 registered in one of 495 UK general practices that contributed medical data to The Health Improvement Network database between 1990-2009. We estimated the incidence of fractures, burns and poisonings by age, sex, socio-economic group and calendar period and adjusted incidence rate ratios (IRR) comparing the least and most socio-economically deprived areas over time. Estimates of the UK annual burden of injuries and the excess burden attributable to deprivation were derived from incidence rates.The cohort of 979,383 children experienced 20,804 fractures, 15,880 burns and 10,155 poisonings, equating to an incidence of 75.8/10,000 person-years (95% confidence interval 74.8-76.9) for fractures, 57.9 (57.0-58.9) for burns and 37.3 (35.6-38.0) for poisonings. Incidence rates decreased over time for burns and poisonings and increased for fractures (p<0.001 test for trend for each injury). They were significantly higher in more deprived households (IRR test for trend p<0.001 for each injury type) and these gradients persisted over time. We estimate that 865 fractures, 3,763 burns and 3,043 poisonings could be prevented each year in the UK if incidence rates could be reduced to those of the most affluent areas.The incidence of burns and poisonings declined between 1990 and 2009 but increased for fractures. Despite these changes, strong socio-economic inequalities persisted resulting in an estimated 9,000 additional medically-attended injuries per year in under-5s.